Methods for optimizing the display conditions of brain magnetic resonance images. - Hara, Toshimasa; Inoue, Yusuke; Ukisu, Ryutaro; Hata, Hirofumi (Japanese Journal of Radiology, 2017)
Purpose: To investigate a method for optimizing the display conditions of brain magnetic resonance (MR) images.Materials and Methods: We retrospectively analyzed brain MR images of 120 adults classified into screening, acute cerebral infarction, and brain tumor groups (n = 40 each). Two observers independently displayed the images on a monitor and optimized the display conditions using the W/L and U/L methods. In the W/L method, the observers manipulated the width and level of the display window, while in the U/L method they manipulated the upper and lower levels of the window. The times required were compared between the two methods. Additionally, the appropriateness of the determined window setting was evaluated visually by the respective observer to exclude the possibility that rough, suboptimal adjustment shortened the adjustment time.Results: For both observers and all groups, the time required for optimization was significantly shorter for the U/L method than for the W/L method. The appropriateness of the window setting for the U/L method was equal to or better than that for the W/L method.Conclusion: Manipulating the upper and lower levels of the display window appears to improve the efficiency of interpreting brain MR images through rapid optimization of the display condition.